Mediating effect of self-coping mechanisms on associations between financial practices and financial security of female-headed households - Ahmad, Siti Yuliandi Ahmad; Sabri, Mohamad Fazli; Abd Rahimc, Husniyah; Osman, Syuhaily (Malaysian Consumer and Family Economics Association (MACFEA), 2016)
Coping process involves contingency actions of individual to alter their cognitive and behaviour to cope with stress encountering events in life. Self-coping mechanisms were examined further as mediating effect between financial practices and financial security among female-headed households in Malaysia. A model was then constructed based on Characteristics Theory, Cognitive of Stress and Coping Theory. A multi-stage random sampling was executed and a self-administered survey was executed to collect data from 600 respondents from six single mother associations at every zone in Malaysia. A structural equation modelling using AMOS software was used to examine mediating effect of self-coping mechanisms in a relationship between financial practices and financial security of female-headed households in Malaysia. The findings support that a significant relationship exists between indirect and mediating models. The study revealed that there is a partial mediating effect of self-coping mechanisms between financial practices and financial security. The role of self-coping mechanisms is crucial to grasp a better understanding of how financial practices and financial security are related to improving the living standards of female-headed households. Implications and limitations of the study are dissussed further.